Considerations on the Role of the SDR. (Policy Papers; Policy Paper ;, 2018)
This paper explores whether a broader role for the SDR could contribute to the smooth functioning and stability of the international monetary system (IMS). Recent staff assessments highlighted that the IMS has displayed considerable resilience. But episodes of stress point also to some weaknesses, including in external adjustment mechanisms; limitations of official liquidity provisions through the Global Financial Safety Net (GFSN); and large-scale reserve accumulation-with systemic side effects. Those weaknesses, together with the expansion of the SDR basket, have renewed interest in the SDR and motivated a discussion of whether there is an economic rationale for a broader SDR role. The paper looks into how those weaknesses can be mitigated by three concepts of the SDR: the official SDR, the reserve asset administered by the IMF (O-SDR); SDR-denominated financial instruments, or 'market SDRs' (M-SDR); and the SDR as a unit of account (U-SDR). However, the paper does not propose specific reform options.